Protein and Polysaccharide Base Biomaterial for The Formation of Composite Bone Scaffold - Hafiz Sultan (AlQalam Journal of Medical and Applied Sciences, 2021)
In the past, bone scaffold was nearly new and best method for fixing the destructed body parts and the development of the tissues. Different types of natural and synthetically made biomaterials have been used by the analyst for the evolution of scaffold. The biomaterial that is derived naturally have some favorable properties such as biodegradable, biocompatible, non-toxic, non-antigenic and are safe in use while synthetic biomaterials have some disadvantages because they are made up of synthetic materials which has low biodegradable properties. But in this paper, we mainly focus on natural biomaterial which is used for formation of composite bone scaffold. Protein and polysaccharides based natural biomaterials used for making scaffold. There is another type of natural biomaterials that is bio-ceramics that joins various body parts such as bones and teeth. The main consideration is to give the short scheme about protein based, polysaccharide based and bio-ceramics based biomaterials and their future prospects.